This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We have f ( 2 0 0 8 ) =3012.
The question asks for f ( 2 0 0 9 ) = f ( 2 0 0 8 + 1 ) = f ( 2 0 0 8 ) + f ( 1 ) = 3 0 1 2 + f ( 1 ) . So, we just have to find f ( 1 ) & we are done!
Now lets plug in values and try to observe a pattern.
f ( 0 ) = 2 f ( 0 ) . Clearly then f ( 0 ) = 0
f ( 1 ) = f ( 1 ) + f ( 0 ) = f ( 1 ) ( unnecessary step just to add to the pattern :D)
f ( 2 ) = f ( 1 ) + f ( 1 ) = 2 f ( 1 )
f ( 3 ) = f ( 2 ) + f ( 1 ) = 3 f ( 1 )
f ( 4 ) = f ( 3 ) + f ( 1 ) = f ( 2 ) + f ( 2 ) = 4 f ( 4 )
.....
Observe that f ( n ) = n f ( 1 ) .
Then, f ( 2 0 0 8 ) = 2 0 0 8 f ( 1 ) ;
Hence, f ( 1 ) = 1.5.